Product Life Cycle Of Rolex Watch / Nas Hanini Nasir ... [et al.] - Nasir, Nas Hanini; Malek, Fatin Athirah; Sahari, Mohd Arrabe (2016)
Hans Wilsdorf, at the age of 24, established a company in London specialising in the distribution of timepieces in 1905. He dreamed of a watch worn on the wrist. At that time, wristwatches were not very precise. However, Hans Wilsdorf could see that they could become not only majestic, but also reliable. Hans Wilsdorf convinced the public of his innovative timepieces by equipping them with small and delicate movements manufactured by a Swiss watchmaking company in Bienne.In 1908, around this time, legend has it that Wilsdorf came up with the name of Rolex. It has been said that Wilsdorf wanted his brand to be easy to pronounced in any language. He said, "I tried combining the letters of the alphabet in every possible way. This gave me some hundred names, but none of them felt quite right. One morning, while riding on the upper deck of a horse-drawn omnibus along Cheapside in the City of London, a genie whispered 'Rolex' in my ear."